The narrow road between desires - Rothfuss, Patrick, 1973- (The kingkiller chronicle, 2023)
"Patrick Rothfuss returns to the Kingkiller Chronicle universe with a stunning reimagining of "The Lightning Tree," expanded to twice its previous length and lavishly illustrated by Nate Taylor. Follow the Kingkiller Chronicle's most charming fae as he schemes his way through the small town of Newarre. While Bast cares nothing for the laws of man, he is beholden to older, deeper laws. And despite his cleverness and care, Bast finds himself forced to choose between betraying his master and helping a hated enemy. Playful, sweet, and sly as Bast himself, The Narrow Road Between Desires explores a previously unseen part of Temerant, and shows a side of Bast we've only glimpsed before. Learn more about Bast as he goes against his better judgement and follows his heart's desire. For after all, what good is wisdom if it keeps you from finding your way to danger and delight?"--